THE PLACE AND FUNCTIONS OF AUXILIARY WORDS IN THE LANGUAGE SYSTEM (Scientific journal of the Fergana State University, 2025)
This article examines the role of auxiliary words in the English and Uzbek language systems, their use in speech, their specific grammatical form and functions.